TATA URUT KATA KLAUSA BAHASA ARAB PADA SYA'IR ABU NAWAS (KAJIAN TIPOLOGI SINTAKSIS) - Nurainun Hasibuan; Mulyadi Mulyadi (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This study examines the order of clause words in Arabic found in the sha'irs of Abu Nawas, a famous poet from the Abbasid period. The main objective of this research is to understand the syntactic structure and how the order of words in clauses is used to convey complex and aesthetic meanings in classical Arabic poetry. In this study, a syntactic typological approach was used to analyze the data. This approach allows researchers to compare syntactic patterns in Arabic with those of other languages, as well as to understand the specific characteristics that distinguish the syntactic structure of Arabic. The research data was taken in the form of Arabic clauses or sentences in the verse of Abu nawas. And the source of the data is obtained from the utterances contained in the verse, which is then analyzed in depth to identify the most dominant word order patterns and prominent syntactic characteristics. Data collected from the Sha'ir Abu Nawas shows that in Arabic, the order of words in sentences is very flexible but has a dominant pattern that most sentences follow. In declarative and imperative sentences, the V-S-O pattern is very dominant, while in interrogative and ismiyyah sentences, the S-V-O and O-V-S patterns are also found. These patterns show that Arabic allows for variations in word order to suit the meaning and focus desired by the writer or poet. This shows the flexibility and structural beauty of the Arabic language, especially in classical poetry.